Characteristics of hospitalizations with an influenza diagnosis, France, 2012‐2013 to 2016‐2017 influenza seasons. Issue 3 (5th February 2020) - Pivette, Mathilde; Nicolay, Nathalie; de Lauzun, Virginie; Hubert, Bruno
Abstract: Background: Estimating the global burden of influenza hospitalizations is required to allocate resources and assess interventions that aim to prevent severe influenza. In France, the current routine influenza surveillance system does not fully measure the burden of severe influenza cases. The objective was to describe the characteristics and severity of influenza hospitalizations by age‐group and by season between 2012 and 2017. Methods: All hospitalizations with a diagnosis of influenza in metropolitan France between July 2012 and June 2017 were extracted from the French national hospital discharge database (PMSI). For each season, the total number of influenza hospitalizations, admissions to intensive care units (ICU), proportion of deaths, lengths of stay, and distribution in diagnosis‐related groups were described by age‐group. Results: Over the five seasons, 91 255 hospitalizations with a diagnosis of influenza were identified. The average influenza hospitalization rate varied from 13/100 000 in 2013‐2014 to 46/100 000 in 2016‐2017. A high rate was observed in elderlies during the 2014‐2015 and 2016‐2017 seasons, dominated by A(H3N2) virus. The youngest were impacted in 2015‐2016, dominated by B/Victoria virus. The proportion of influenza hospitalizations with ICU admission was 10%, and was higher in age‐group 40‐79 years. The proportion of deaths and length of stay increased with age. Conclusions: The description of influenza hospitalizations recorded in the PMSI give key information on the burden of severe influenza in France. Analyses of these data annually is valuable in order to document the severity of influenza hospitalizations by age‐group and according to the circulating influenza viruses.